2011
DOI: 10.1007/s12033-011-9428-0
|View full text |Cite
|
Sign up to set email alerts
|

The High-Level Expression of Human Tissue Plasminogen Activator in the Milk of Transgenic Mice with Hybrid Gene Locus Strategy

Abstract: Transgene expression for the mammary gland bioreactor aimed at producing recombinant proteins requires optimized expression vector construction. Previously we presented a hybrid gene locus strategy, which was originally tested with human lactoferrin (hLF) as target transgene, and an extremely high-level expression of rhLF ever been achieved as to 29.8 g/l in mice milk. Here to demonstrate the broad application of this strategy, another 38.4 kb mWAP-htPA hybrid gene locus was constructed, in which the 3-kb geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Therefore, future studies should examine how to control the locus and construct an efficient expression vector in transgenic animals, and how to select expression vectors for specific recombinant proteins, eventually identifying an ideal expression vector and animal species to express different recombinant proteins. The yield must also be further improved by optimization of the expression vector construction or other methods (1)(2)(3)(4)(39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, future studies should examine how to control the locus and construct an efficient expression vector in transgenic animals, and how to select expression vectors for specific recombinant proteins, eventually identifying an ideal expression vector and animal species to express different recombinant proteins. The yield must also be further improved by optimization of the expression vector construction or other methods (1)(2)(3)(4)(39)(40)(41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be caused by the different proteins or inherent factors of the different species (mice and goats). hLF and hLA were expressed by different milk protein regulatory sequences, and the high-expression level of two different foreign proteins driven by the same mouse whey acidic protein gene locus was obtained [2, 5]. However, Yu et al [3] reported that the intron added in the coding sequence of hLF cDNA played an important role in efficient expression of rhLF and that milk levels of rhLF increased from 0.8 to 36 mg/mL, when derived by the same goat β -casein gene.…”
Section: Discussionmentioning
confidence: 99%
“…Construction of the targeting vector is one of the most important techniques for mammary gland bioreactors, but the currently available techniques are laborious, time consuming, and inefficient [3]. Constructs with milk protein gene loci could be an ideal strategy for high level expression of foreign genes [2, 4, 5], but it is often difficult to manipulate the large size of the vector into donor cells for nuclear transfer [3, 6]. In our previous studies [7], a hybrid milk protein promoter (goat β -casein, bovine α s1-casein, and goat β -lactoglobulin (BLG)) with cytomegalovirus (CMV) enhancer was constructed and the expression level of recombinant human lactoferrin in the milk of transgenic mice was up to 8.2 mg/mL, which was more effective than using a single milk protein promoter (7–40 ng/mL).…”
Section: Introductionmentioning
confidence: 99%
“…Next, mammary glands were gently massaged and milked with tweezers. According to the method described previously 43 44 , milk collection was slightly modified and started on day 8 after delivery. Briefly, samples were collected 3 times each day, 100 μl each time, and continually for 5 days.…”
Section: Methodsmentioning
confidence: 99%